2021
DOI: 10.1101/2020.12.26.20248886
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Gut Microbiota Markers for Antipsychotics Induced Metabolic Disturbance in Drug Naïve Patients with First Episode Schizophrenia – A 24 Weeks Follow-up Study

Abstract: BackgroundWhile cardiometabolic adverse effects associated with antipsychotic treatment is an important clinical challenge, the underlying mechanisms are unknown. Here we investigated if changes in gut microbial composition associate with the metabolic disturbance induced by the risperidone treatment of schizophrenia.MethodsNinety-four first episode, drug naïve schizophrenia patients (SZ), and 100 healthy controls (HCs) were enrolled at baseline. Six metabolic parameters (glucose, homeostasis model assessment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 44 publications
(60 reference statements)
0
3
0
Order By: Relevance
“…41 Another study reported that risperidone treatment for 24 weeks caused a significant change in the abundance of Bacteroidetes, Christensenellaceae, Enterobacteriaceae, and Proteobacteria, which was associated with the changes in metabolic parameters such as increased BMI, HOMA-IR, and serum lipids. 81 On the contrary, 6 weeks of olanzapine treatment in an observational study caused significant weight gain but did not change the GMB composition in SCZ patients. 54 In a nutshell, the GMB could be regarded as a potential player in metabolic perturbations associated with AP treatment.…”
Section: Therapeutic Advances In Psychopharmacologymentioning
confidence: 92%
See 1 more Smart Citation
“…41 Another study reported that risperidone treatment for 24 weeks caused a significant change in the abundance of Bacteroidetes, Christensenellaceae, Enterobacteriaceae, and Proteobacteria, which was associated with the changes in metabolic parameters such as increased BMI, HOMA-IR, and serum lipids. 81 On the contrary, 6 weeks of olanzapine treatment in an observational study caused significant weight gain but did not change the GMB composition in SCZ patients. 54 In a nutshell, the GMB could be regarded as a potential player in metabolic perturbations associated with AP treatment.…”
Section: Therapeutic Advances In Psychopharmacologymentioning
confidence: 92%
“…Li et al 81 Country: China Study design: 94 drug naïve, first-episode SCZ patients and 100 HCs were enrolled in the study. Metabolic parameters such as BMI, fasting blood glucose, total cholesterol, LDL cholesterol, HDL cholesterol, insulin, and HOMA-IR were measured.…”
mentioning
confidence: 99%
“…Chronic use of RIS led to an increase in the subjects' body mass index (BMI) and a significantly lower ratio of Bacteroidetes to Firmicutes compared to the control group. Li et al (2021) observed that after 24 weeks of RIS treatment, BMI, glucose, Homeostatic Model Assessment (HOMA-IR), Total-cholesterol, low-density lipoprotein cholesterol (LDL-C), high-density lipoprotein cholesterol (HDL-C) and triglyceride levels were significantly changed compared to pre-treatment values. It was also found that the baseline abundance of Christensenellaceae and Enterobacteriaceae was significantly associated with changes in triglycerides, BMI and HOMA-IR after 24 weeks of RIS treatment.…”
Section: Antipsychoticsmentioning
confidence: 99%